2010
DOI: 10.1104/pp.110.157800
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Metabolites Regulated in Root Hairs in Response to the Symbiotic BacteriumBradyrhizobium japonicum     

Abstract: Nodulation of soybean (Glycine max) root hairs by the nitrogen-fixing symbiotic bacterium Bradyrhizobium japonicum is a complex process coordinated by the mutual exchange of diffusible signal molecules. A metabolomic study was performed to identify small molecules produced in roots and root hairs during the rhizobial infection process. Metabolites extracted from roots and root hairs mock inoculated or inoculated with B. japonicum were analyzed by gas chromatography-mass spectrometry and ultraperformance liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
89
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 141 publications
(97 citation statements)
references
References 151 publications
3
89
0
5
Order By: Relevance
“…The invasion of plant tissues toward the nodule requires the cells to traverse a stressful environment (43)(44)(45)(46), and it was observed that B. japonicum cells that are deficient in ␣-ketoglutarate dehydrogenase produce nodule primordia that abort at higher rates. This observation suggests that energy must be efficiently produced by the rhizobia to complete root infection (47).…”
Section: Discussionmentioning
confidence: 99%
“…The invasion of plant tissues toward the nodule requires the cells to traverse a stressful environment (43)(44)(45)(46), and it was observed that B. japonicum cells that are deficient in ␣-ketoglutarate dehydrogenase produce nodule primordia that abort at higher rates. This observation suggests that energy must be efficiently produced by the rhizobia to complete root infection (47).…”
Section: Discussionmentioning
confidence: 99%
“…In order to understand the processes behind rhizobial infection and nodule development, a number of studies have identified genes, proteins, and metabolites regulated during the interaction between legume host species and rhizobia (Benedito et al 2008;Brechenmacher et al 2008Brechenmacher et al , 2009Brechenmacher et al , 2010Desbrosses et al 2005;Libault et al 2010a;Lim et al 2010;Lohar et al 2006;Oehrle et al 2008;Wan et al 2005). These studies have implicated a large number of genes, proteins, and metabolites involved in signal transduction, plant defense, carbon and nitrogen metabolism, and nutrient exchange during establishment of RNS.…”
mentioning
confidence: 99%
“…Over the last decade, various large-scale approaches such as transcriptomics, proteomics, and metabolomics, have been used to dissect the legume-rhizobia symbiosis (27)(28)(29). However, most of these studies looked at relatively late responses to rhizobia or NF and unfortunately were not integrated.…”
mentioning
confidence: 99%